Optimality Theory in Phonology 2004
DOI: 10.1002/9780470756171.ch6
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Computable Functions in Optimality Theory

Abstract: Is Optimality Theory a constraining theory? A formal analysis shows that it is, if two auxiliary assumptions are made: (1) that only markedness and faithfulness constraints are allowed, and (2) that input and output representations are made from the same elements. Such OT grammars turn out to be incapable of computing circular or infinite chain shifts. These theoretical predictions are borne out by a wide range of natural phonological processes including augmentation, alternations with zero, metathesis, and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
2
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(78 citation statements)
references
References 20 publications
1
70
2
5
Order By: Relevance
“…This generalization, stated originally in (Anderson and Browne, 1973) for exchange rules, and extended to circular chain shifts in (Moreton, 2004), raises the fascinating question, why are circular chain shifts always morphological in nature?…”
Section: Analysis Of the Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…This generalization, stated originally in (Anderson and Browne, 1973) for exchange rules, and extended to circular chain shifts in (Moreton, 2004), raises the fascinating question, why are circular chain shifts always morphological in nature?…”
Section: Analysis Of the Problemmentioning
confidence: 99%
“…To understand the problem posed by exchange rules, it is necessary to review the results of some prior work, beginning with the formal analysis of circular chain shifts in (Moreton, 2004). This work showed that in a version of Optimality Theory characterized by the assumptions below, certain collections of mappings are not computable.…”
Section: Analysis Of the Problemmentioning
confidence: 99%
See 3 more Smart Citations